2024
DOI: 10.1038/s41586-024-07182-w
|View full text |Cite
|
Sign up to set email alerts
|

A distinct Fusobacterium nucleatum clade dominates the colorectal cancer niche

Martha Zepeda-Rivera,
Samuel S. Minot,
Heather Bouzek
et al.

Abstract: Fusobacterium nucleatum (Fn), a bacterium present in the human oral cavity and rarely found in the lower gastrointestinal tract of healthy individuals1, is enriched in human colorectal cancer (CRC) tumours2–5. High intratumoural Fn loads are associated with recurrence, metastases and poorer patient prognosis5–8. Here, to delineate Fn genetic factors facilitating tumour colonization, we generated closed genomes for 135 Fn strains; 80 oral strains from individuals without cancer and 55 unique cancer strains cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(20 citation statements)
references
References 78 publications
0
19
1
Order By: Relevance
“…Nonetheless, all analyses confirmed that four genomes that include strains FNU and 13-08-02 (in clade C1 in Zepeda-Rivera et al) do not belong to the F. nucleatum animalis subspecies or any other known species/subspecies. Thus, our data do not support the previously suggested division of F. nucleatum animalis diversity in two clades 6 . In their recent study, Zepeda-Rivera and coworkers showed that clade C2 was associated to the CRC niche, whereas C1 was not.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Nonetheless, all analyses confirmed that four genomes that include strains FNU and 13-08-02 (in clade C1 in Zepeda-Rivera et al) do not belong to the F. nucleatum animalis subspecies or any other known species/subspecies. Thus, our data do not support the previously suggested division of F. nucleatum animalis diversity in two clades 6 . In their recent study, Zepeda-Rivera and coworkers showed that clade C2 was associated to the CRC niche, whereas C1 was not.…”
Section: Discussioncontrasting
confidence: 99%
“…Indeed, all these features were compared between two distinct species, although closely related. Whereas this is unlikely to change the conclusion that F. nucleatum animalis is associated with CRC, our data call for a re-assessment of the characteristics of clade C2, which were established in comparison to a different species 6 . This is particularly true in light of the PCA and STRUCTURE analyses, which indicated that the new specie/clade C1 and F. nucleatum animalis belong to different clusters or modern populations.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations